Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.pupt.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro aerodynamic characterization of the dose emitted during nebulization of tobramycin high strength solution by novel and jet nebulizer delivery systems

Abstract: The HSTS can be nebulized by all tested nebulisers but the high frequency NE-U22 Omron(®) and Aeroneb Go(®) are more efficient. When the HSTS compared to TOBI(®), the respirable inhaled dose was increased to more than 73%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…14 In addition, a recent report demonstrated variability from different manufacturers using the same dose of tobramycin. 15 It therefore remains uncertain whether mesh technology provides reproducible drug delivery for repeated use in a typical clinical trial. The primary objective of this study was to determine the reliability of the Aerogen Solo vibrating mesh nebulizer to repeatedly deliver the expected dose of a test aerosol.…”
Section: Introductionmentioning
confidence: 99%
“…14 In addition, a recent report demonstrated variability from different manufacturers using the same dose of tobramycin. 15 It therefore remains uncertain whether mesh technology provides reproducible drug delivery for repeated use in a typical clinical trial. The primary objective of this study was to determine the reliability of the Aerogen Solo vibrating mesh nebulizer to repeatedly deliver the expected dose of a test aerosol.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence supporting the use of mesh ( Fig. 1a and b) rather than jet nebulizers for nebulized antibiotic delivery [1,3,11,15]. In vitro, mesh nebulizers appear superior over jet nebulizers to deliver tobramycin [15].…”
Section: Optimisation Of Nebulization To Maximize Antibiotic Lung Depmentioning
confidence: 91%
“…1a and b) rather than jet nebulizers for nebulized antibiotic delivery [1,3,11,15]. In vitro, mesh nebulizers appear superior over jet nebulizers to deliver tobramycin [15]. Aerosol particle size is slightly smaller with jet nebulizers compared to mesh nebulizers, but always remained below five microns, a condition required to reach the distal lung.…”
Section: Optimisation Of Nebulization To Maximize Antibiotic Lung Depmentioning
confidence: 99%
“…A limitation of this and other studies is its in vitro nature. [1][2][3][4][5][6][7]11 For some drugs with a flat dose-response curve, a more efficient device might not be better; for other drugs with a narrow therapeutic window, a low coefficient of variation will be of paramount importance for safety. The next step is to determine whether these differences in drug-delivery efficiency are clinically important.…”
Section: See the Original Study On Page 1419mentioning
confidence: 99%
“…The use of vibrating mesh nebulizers has been limited by poor performance with some formulations (eg, tobramycin and hypertonic saline) and reported problems with reliability. [4][5] There has been a paucity of technological development in the area of drug-delivery devices intended to be used with patients receiving mechanical ventilation. Cuccia et al 6 recently reported a new type of nebulizer that operates using a breath-enhancement mechanism and is placed before the inspiratory limb.…”
mentioning
confidence: 99%